ANALYSIS OF THE SOURCES AND EFFECT OF EXTENSION INFORMATION ON OUTPUT OF WOMEN MAIZE FARMERS IN SOBA LOCAL GOVERNMENT AREA OF KADUNA STATE, NIGERIA - Adegboye, G. A.; Oyinbo, O.; Owolabi, J. O.; Hassan, O. S. (European Scientific Journal, ESJ, 2013)
The study was carried out to examine the sources of extension information among women maize farmers and the effect of extensive information on the output of the farmers in the study area. Primary and secondary data were utilized in this study. The primary data were obtained using a structured questionnaire and were analyzed using the instrumentality of descriptive and inferential statistics. The result of the data analysis showed that a large proportion (64.5%) of the respondents indicated that radio was their main source of extensive information, 59% of the respondents indicated that visit by extension agents was their main source of extensive information. The mean output (1946.53kg) for women farmers with access to extensive information was significantly higher than the mean output of women farmers without extension information (1456.94kg) at the 1 percent probability level. Based on the findings of this study, it is recommended that the transfer of extension information to women maize farmers should be strongly strengthened as extension information is significant in enhancing the output of the women maize farmers in the study area.